The impact of delirium on withdrawal of life-sustaining treatment after intracerebral hemorrhage. (17th November 2020) - Reznik, Michael E.; Moody, Scott; Murray, Kayleigh; Costa, Samantha; Grory, Brian Mac; Madsen, Tracy E.; Mahta, Ali; Wendell, Linda C.; Thompson, Bradford B.; Rao, Shyam S.; Stretz, Christoph; Sheth, Kevin N.; et al.
Abstract : Objective: To determine the impact of delirium on withdrawal of life-sustaining treatment (WLST) after intracerebral hemorrhage (ICH) in the context of established predictors of poor outcome, using data from an institutional ICH registry. Methods: We performed a single-center cohort study on consecutive patients with ICH admitted over 12 months. ICH features were prospectively adjudicated, and WLST and corresponding hospital day were recorded retrospectively. Patients were categorized using DSM-5 criteria as never delirious, ever delirious (either on admission or later during hospitalization), or persistently comatose. We determined the impact of delirium on WLST using Cox regression models adjusted for demographics and ICH predictors (including Glasgow Coma Scale score), then used logistic regression with receiver operating characteristic curve analysis to compare the accuracy of ICH score–based models with and without delirium category in predicting WLST. Results: Of 311 patients (mean age 70.6 ± 15.6, median ICH score 1 [interquartile range 1–2]), 50% had delirium. WLST occurred in 26%, and median time to WLST was 1 day (0–6). WLST was more frequent in patients who developed delirium (adjusted hazard ratio 8.9 [95% confidence interval (CI) 2.1–37.6]), with high rates of WLST in both early (occurring ⩽24 hours from admission) and later delirium groups. An ICH score-based model was strongly predictive of WLST (area under the curve [AUC] 0.902 [95% CI 0.863–0.941]), and the addition of delirium category further improved the model's accuracy (AUC 0.936 [95% CI 0.909–0.962], p = 0.004). Conclusion: Delirium is associated with WLST after ICH regardless of when it occurs. Further study on the impact of delirium on clinician and surrogate decision-making is warranted.